In Vitro Comparison of Compressive and Tensile Strengths of Acrylic Resins Reinforced by Silver Nanoparticles at 2% and 0.2% Concentrations - Tahereh Ghaffari; Fahimeh Hamedirad; Baharak Ezzati (Tabriz University of Medical Sciences, 2014)
Background and aims. Polymethyl methacrylate, PMMA, is widely used in prosthodontics for fabrication of removable prostheses. This study was undertaken to investigate the effect of adding silver nanoparticles (AgNPs) to PMMA at 2% and 0.2% concentrations on compressive and tensile strengths of PMMA. Materials and methods. The silver nanoparticles were mixed with heat-cured acrylic resin in an amalgamator in two groups at 0.2 and 2 wt% of AgNPs. Eighteen 2×20×200-mm samples were prepared for tensile strength test, 12 samples containing silver nanoparticle and 6 samples for the control group. Another 18 cylindrical 25×38-mm samples were prepared for compressive strength test. Scanning electron microscopy was used to verify homogeneous distribution of particles. The powder was manually mixed with a resin monomer and then the mixture was properly blended. Before curing, the paste was packed into steel molds. After curing, the specimens were removed from the molds. One-way ANOVA was used for statistical analysis, followed by multiple comparison test (Scheffé's test). Results. This study showed that the mean compressive strength of PMMA reinforced with AgNPs was significantly higher than that of the unmodified PMMA (P<0.05). It was not statistically different between the two groups reinforced with AgNPs. The tensile strength was not significantly different between the 0.2% group and unmodified PMMA and it decreased significantly after incorporation of 2% AgNPs (P<0.05). Conclusion. Based on the results and the desirable effect of nanoparticles of silver on improvement of compressive strength of PMMA, use of this material with proper concentration in the palatal area of maxillary acrylic resin dentures is recommended.